Hepatoprotective Effects of Nasturtium Officinale and Allium Polyanthum Extracts on CCL4- Induced Hepatic Damage In Albino Rats - Shkar Rzgar K.Rostam; Zana Hassan Ibrahim; Rebaz Rebwar Mala; Soran Qadir Abdul (Kurdistan Journal of Applied Research)
The aim: This study was designed to explore the potential hepatoprotective effects of Nasturtium officinale and Allium polyanthum plant extracts against CCl4-induced hepatic injury in rat model.